Preparation of cobalt-modified montmorillonite for corrosion inhibition of 2024-T3 aluminium alloy surface - Thai, Thu Thuy; Pham, Gia Vu; Trinh, Anh Truc (Vietnam Journal of Science and Technology, 2024)
In this study, cobalt Co(II) cations were incorporated into the interlayer spaces of the montmorillonite matrix via a cation-exchange reaction, leading to an increase in layer spacing as Na was replaced by Co, as demonstrated by x-ray diffraction analysis. It was observed that Co could be released from the MMTCo matrix into the aqueous medium, with this release being more pronounced in alkaline environments. Electrochemical impedance spectroscopy (EIS) confirmed that MMTCo acts as an effective corrosion inhibitor for the AA2024 surface, with its inhibitive efficiency being concentration-dependent and more significant at higher concentrations. FE-SEM imaging revealed that a protective layer formed on the AA2024 surface immersed in a filtrate containing MMTCo, in contrast to surfaces exposed to the filtrate of MMT, which were significantly attacked.